Gut microbiota linked to autoimmune uveitis - Horai, Reiko (Annals of Eye Science, 2017)
Autoimmune uveitis is a group of intraocular inflammatory diseases that arise without known infectious etiology. Uveitis is one of the leading causes of blindness in the developed world and is responsible for up to 15% of severe visual handicap. The disease affects population of working age and has a significant impact on public health. Patients often show detectable immune responses to unique retinal proteins such as retinal arrestin and interphotoreceptor retinoid binding protein (IRBP), which are involved in visual function, and particular HLA haplotypes have been associated with disease, supporting the autoimmune nature (1). Although anecdotal evidence suggested a link between microbial infections and uveitis, our understanding of the etiology of disease, its driving mechanisms and treatment options are still limited. Animal models have been instrumental to advance our understanding on pathogenesis of uveitis. A ‘classic’ uveitis model in mice is referred as experimental autoimmune uveitis (EAU), involving active immunization with IRBP in complete Freund’s adjuvant (CFA) that contains heat-killed Mycobacterium tuberculosis. Co-administration of bacterial adjuvants is required to activate innate immune cells and create the proinflammatory milieu to induce adaptive immune responses and to trigger the autoimmune effector pathway (1). However, unlike experimental diseases in the animal models, most cases of human autoimmune uveitis cannot be connected to an exposure of the immune system to ocular antigens that are present behind the blood retinal barrier. These target antigens in uveitis are sequestered inside the eye and are not expressed in the periphery (2), but retina-specific T cells that would recognize them must be activated to enter the eye to drive pathology in uveitis. This presents a paradox and raises a fundamental question: where and how do autoreactive T cells, that can recognize retinal antigens and trigger uveitis, first become activated?